The role of bacteria in gallstone formation - Wang, Danfeng; Ye, Aihui; Jiang, Ni (Folia microbiologica, 2024)
Gallstones are a prevalent biliary system disorder that is particularly common in women. They can lead to various complications, such as biliary colic, infection, cholecystitis, and even gallbladder cancer. However, the etiology of gallstones remains incompletely understood. The significant role of bacteria in gallstone formation has been demonstrated in recent studies. Certain bacteria not only influence bile composition and the gallbladder environment but also actively participate in stone formation by producing enzymes such as β-glucuronidase and mucus. Therefore, this review aimed to analyze the mechanisms involving the types and quantities of bacteria involved in gallstone formation, providing valuable references for understanding the etiology and clinical treatment of gallstones.
Keywords: žlučové kameny; lidé; Female; Bile components; Gallstones; žluč; Gallbladder internal environment; Bacteria; Bile; Formation; ženské pohlaví; Humans